2019
DOI: 10.3390/ijerph17010080
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Determinants of Discretionary Food Intake in a Cohort of Australian Children Aged 12–14 Months

Abstract: Despite recommendations to the contrary, consumption of discretionary (energy-dense, nutrient-poor) foods begins for some children early in the weaning period, and the proportion of children consuming discretionary foods increases markedly in the second year of life. The purpose of this study was to determine intake and sources of discretionary foods in a cohort of 828 Australian toddlers (mean age: 13.1mo), and to identify determinants of discretionary food intake. At approximately 12 months of age, 3 non-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
6
21
0
Order By: Relevance
“…The Australian Bureau of Statistics estimates that one in four (24.6%) 2–4-year-olds are overweight or obese [ 7 ]. Studies of Australian children aged less than 2 years indicate that the consumption of discretionary foods that are energy dense and nutrient poor begins early in the weaning period and increases markedly in the second year of life [ 8 , 9 , 10 ]. Additionally, parents and children living with social disadvantage are at greater risk of poor health, including being overweight or obese and, therefore, should be a priority for interventions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Australian Bureau of Statistics estimates that one in four (24.6%) 2–4-year-olds are overweight or obese [ 7 ]. Studies of Australian children aged less than 2 years indicate that the consumption of discretionary foods that are energy dense and nutrient poor begins early in the weaning period and increases markedly in the second year of life [ 8 , 9 , 10 ]. Additionally, parents and children living with social disadvantage are at greater risk of poor health, including being overweight or obese and, therefore, should be a priority for interventions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complete dietary data for all 3 days were available for 828 children. Previous investigations of population parameters have found that the sample characteristics of this cohort are diverse and generally representative of the total South Australian Births that year [ 19 , 21 , 26 ]. The majority of participating mothers were aged between 25 and 34 years of age, had commenced or completed university studies, were born in Australia or New Zealand, and had one or two children ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been suggested that less stringent parenting practices are employed in multiple‑child families when compared to single‑child families [ 50 ] and that a child’s food exposures are shaped by the food preferences of older siblings [ 45 , 51 ]. These factors may lead to a greater consumption of energy‑dense, nutrient‑poor, non‑core foods and drinks within multiple‑child families [ 19 , 52 ], which may displace foods high in wholegrain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 At 1 year, 96% of children had consumed discretionary foods, which contributed on average 11.2% of total energy. 29 Between 1 and 2 years, intake of free sugars increased sharply, contributing 3.6% (IQR: 1.6–4.8) of total energy intake at 1 and 22.5% at 2 years (IQR: 12.8–37.7). 30 The proportion of participants that exceeded the WHO recommendations that <10% of energy should come from free sugars 9 increased substantially from 1 (2.5%) to 2 years (38.0%).…”
Section: Key Findings To Datementioning
confidence: 97%